Defective two-dimensional layered heterometallic phosphonates as highly efficient oxygen evolution electrocatalysts. Issue 20 (19th August 2021) - Yan, Chong-Chong; Tang, Si-Fu
Abstract : Two-dimensional metal phosphonates can be used as OER catalysts directly and their catalytic performances can be improved greatly by combining heterometal doping and defect engineering methods. Abstract : High-performance nonprecious electrocatalysts toward water splitting are in high demand but currently their development is still challenging. Here, we demonstrate that heterometallic two-dimensional (2D) metal phosphonates with improved catalytic activity and durability could be realized through defect engineering and heterometallic doping. The optimal electrocatalyst QAU-1-FeNi(1:2) exhibits prominent oxygen evolution reaction (OER) activity in alkaline electrolytes with a very low overpotential of 230 mV at 10 mA cm −2 and a small Tafel slope of 47 mV dec −1 and is superior to the commercial electrocatalyst IrO2 . Meanwhile, QAU-1-FeNi(1:2) shows outstanding stability for at least 20 hours and continuous CV scanning for more than 2000 cycles. In this work, a novel strategy of optimization of phosphonate based electrocatalysts by defect engineering and heterometallic doping has been proposed, which has significant potential in the preparation of catalysts for energy conversion applications.